Fool for Christ: The Political Thought of J.S. Woodsworth - Mills, Allen (University of Toronto Press, 1991)
James Shaver Woodsworth (1874-1942) stands as one of the half-dozen most important national political figures in twentieth-century Canadian history. Allen Mills acknowledges his outstanding achievements while providing a critical account of the Woodsworth legacy and revising the received opinion of him as a man of unbending conviction and ever-coherent principle. A product of western Canada's pioneer society and a stern Methodist household, Woodsworth grew up to make his way into social service and politcal action. A member of parliament for over twenty years, he rejected the traditional forms of political activity, seeking a new politics and a new political party. The latter turned out to be the Co-operative Commonwealth Federation founded in 1932. Its first leader was Woodsworth himself. In a crucial period between the World Wars, Woodsworth helped define the character of the modern Canadian, non-Marxist Left and of many of Canada's important economic and social institutions. Among them are the welfare state, the Bank of Canada, and Canada's internationalist role in the contemporary world.--Publisher's description.